50 Years After the Creation of Communication Careers: the Distance Between Training and the Market - Blanco, Cecilia (2022)
There is abundant literature on the distance between the training of Latin American communication and journalism graduates and the labor market demands. However, few studies are concerned with a historiographic analysis of the reasons for such distance. In order to understand these causes, we carried out a systematic historiographic documentary research. We worked with digital repositories and incorporated articles published in indexed journals, books and chapters from books by some of the region’s most renowned communication professionals. The results show that to prevent graduates from being marginalized by the market, it would be necessary for communication faculties to comprehensibly study the characteristics and evolution of the socio-productive system and the market, as well as the characteristics and evolution of curricula. Apart from this aspect, which we consider crucial, it would be relevant to analyze the educational and professional trajectories of these professionals longitudinally, and to conduct interdisciplinary and transdisciplinary research on the problems of present-day society in order to draw heuristic maps and develop flexible and updated study programs.